Pengaruh Atribut Produk, Harga, Kebutuhan Mencari Variasi dan Ketidakpuasan Konsumen terhadap Keputusan Perpindahan Merek dari Samsung Galaxy Series di Kota Malang - Arianto, Anandhitya Bagus (Jurnal Aplikasi Manajemen, 2013)
The purpose of this study is to analyze the influence of product attributes, prices, the need to find variations and dissatisfaction on brand switching decisions toward Samsung Galaxy series. The population of this research is consumers who use smartphone with Android operating system, with sample number as many as 100 respondents. Data analysis in this study uses multiple regression. The results showed thatthe product attributes and prices provides significant but negative effect on brand switching decisions; meanwhile, the need for variation and dissatisfaction brings positive and significant impact on brand switching decisions. In order to avoid brand switching behavior, the company developed a marketing strategy by making innovations on product attributes and making proper pricing that suits the needs ofconsumers. In addition, Samsung's strategy to attract potential buyers is by giving promotions and attractive discounts. The company must continuously create a good brand image for Samsung smartphone brand. This is done as an effort to build a strong brand. Through the company's strong brand image, it can satisfy the customer and minimize customers to seek for product variations other than Samsung smartphone brand.